2018
DOI: 10.1590/1981-22562018021.180011
|View full text |Cite
|
Sign up to set email alerts
|

The experience of spirituality among institutionalized elderly people

Abstract: Objective: To identify the meanings attributed to the experience of spirituality when faced with life situations among elderly persons living in a long-term care facility. Method: A qualitative, exploratory and descriptive survey was carried out, based on interviews with eight elderly people living in a long-term care facility for the elderly in the state of Rio Grande do Sul, Brazil. Results: The content that emerged from the interviews underwent qualitative analysis for the extraction of units of significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
(18 reference statements)
0
9
0
11
Order By: Relevance
“…al. ; A teoria do conforto é vital no cuidado de enfermagem em todos os contextos, visto que possibilita ter o olhar holístico sobre o idoso e, dessa forma envolve os mesmos no exercício da autonomia e da independência a partir das suas necessidades humanas básicas, as quais contempla as dimensões do conforto (Scortegagna et al, 2018;Cardoso et al, 2019).…”
Section: Discussionunclassified
“…al. ; A teoria do conforto é vital no cuidado de enfermagem em todos os contextos, visto que possibilita ter o olhar holístico sobre o idoso e, dessa forma envolve os mesmos no exercício da autonomia e da independência a partir das suas necessidades humanas básicas, as quais contempla as dimensões do conforto (Scortegagna et al, 2018;Cardoso et al, 2019).…”
Section: Discussionunclassified
“…Outro ponto relevante que se relaciona com o envelhecimento se prende com a questão das incapacidades, que remete para a aceitação da inevitável mudança, que é diferenciada de idoso para idoso. A esse nível, a religiosidade assume um papel positivo no enfrentar das incapacidades, sendo um importante mecanismo no reforço do bem-estar e do funcionamento mental (Moberg, 2008;Scortegagna et al, 2018).…”
Section: Introductionunclassified
“…mostram ainda que a religiosidade em adultos mais velhos se correlaciona, positivamente, com a frequência e qualidade das interações familiares intergeracionais, assim como proporciona redes de convívio mais alargadas e apoiantes, resultando quase sempre em mudanças positivas ao nível da saúde mental (Pargament & Ano, 2004;Scortegagna et al, 2018;Wink & Dillon, 2008). Autores que estudam esta temática (Moreira-Almeida et al, 2006) identificaram 850 artigos sobre vários países -publicados ao longo do século XX e na primeira década do século XXI -que comprovam que indivíduos mais religiosos possuem maior/melhor qualidade de vida e, por conseguinte, apresentam melhores índices de funcionamento mental.…”
Section: Introductionunclassified
“…Similarly, investigations showed that psychological factors and age may influence happiness in older adults who are living in the community (Luchesi et al, 2018). Scortegagna, Pichler, and Fáccio (2018) indicated that Spirituality can increase happiness among institutionalized elderly individuals. Adib-Hajbaghery and Faraji (2015) showed that most of the elders who living in the community and in sanitariums have significantly lower happiness.…”
Section: Introductionmentioning
confidence: 99%